Phénoménologie queer: orientations, objets et autres - Ahmed, Sara (Éditions de la rue Dorion, 2022)
En se concentrant sur l’aspect « orientation » de l’« orientation sexuelle », Sara Ahmed examine ce que signifie pour les corps le fait d’être situés dans l’espace et le temps. Les corps prennent forme lorsqu’ils se déplacent dans le monde en se dirigeant vers ou loin des objets et des autres. Être « orienté » signifie se sentir chez soi, savoir où l’on se trouve, ou avoir certains objets à portée de main. Les orientations affectent ce qui est proche du corps ou ce qui peut être atteint. Selon Sara Ahmed, une phénoménologie queer révèle comment les relations sociales sont organisées dans l’espace, comment la queeresse perturbe et réordonne ces relations en ne suivant pas les chemins acceptés, et comment une politique de désorientation met à portée de main d’autres objets, ceux qui pourraient, à première vue, sembler dérangeants. Dans cet ouvrage fondateur de la réflexion sur le genre écrit en 2006, Sara Ahmed propose qu’une phénoménologie queer puisse étudier non seulement comment le concept d’orientation est informé par la phénoménologie, mais aussi l’orientation de la phénoménologie elle-même. En développant un modèle queer d’orientation, elle combine des lectures de textes phénoménologiques – de Husserl, Heidegger, Merleau-Ponty et Fanon – avec des idées tirées des études queer, de la théorie féministe, de la théorie critique des races, du marxisme et de la psychanalyse.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; féminisme décolonial; har4600; identités LGBTQIA2+; orientation; philosophie; phénoménologie; premier cycle; queer; ressource en ligne; sciences humaines; soc2014; thématiques; études critiques de la race; études féministes

Towards a decolonial feminism - Lugones, Maria (Hypatia, 2010)
Dans « Heterosexualism and the Colonial/Modern Gender System » (Lugones 2007), j’ai proposé de lire la relation entre le colonisateur et le colonisé en termes de genre, de race et de sexualité. Je n’entendais pas par là ajouter une lecture genrée et une lecture raciale aux relations coloniales déjà comprises. J’ai plutôt proposé une relecture de la modernité coloniale capitaliste moderne elle-même. C’est parce que l’imposition coloniale du genre traverse les questions d’écologie, d’économie, de gouvernement, de relations avec le monde des esprits et de connaissance, ainsi que les pratiques quotidiennes qui nous habituent à prendre soin du monde ou à le détruire. Je propose ce cadre non pas comme une abstraction de l’expérience vécue, mais comme une lentille qui nous permet de voir ce qui est caché de notre compréhension de la race et du genre et de la relation de chacun avec l’hétérosexualité normative.
Keywords: amériques; approches et analyses; colonialité du genre; corps; discipline; féminisme décolonial; histoire et politique; hétérosexisme; philosophie; philosophie politique; racisme; régions géographiques; sciences humaines; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Transformations : thinking through feminism, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". -- Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme